(untitled) (Research, Society and Development, 2020)
The subject of this study involves 3D printing technology. Despite the much-vaunted growth and timeliness of this technology, which should not be completely refuted, 3D printing with its respective stage of technological development has been present since 1984, when Charles Hull invented the process of stereolithography. The problem lies in seeking printing that allows printing with different materials on personal printers. Thus, the objective of this study is to design and develop an extrusion system for 3D printers, based on FDM technology, with low cost and capable of working with two different materials. The research is exploratory in nature and was developed by the experimental method with laboratory analysis. In the context it has been taken into account that the main component of a 3D printer is its extruder module, it has been found that most personal printers still use extruder modules capable of working with only one material at a time. In this sense, the result of this project was the development of an extruder module capable of working with two different materials, expanding the capacity of most printers sold for personal use. Therefore, it was perfectly possible, with the methodology used, to meet the objective of designing and developing an extrusion system for 3D printers, based on FDM technology, with low cost and with the ability to work with two different materials simultaneously.